Report on the outcome of Task 3.2: Measures from policy makers - Zis, Thalis; Panagakos, George; Kronbak, Jacob; Psaraftis, Harilaos N. (My University, 2017)
This report summarizes the main research findings of Task 3.2 (entitled “Measures from policy makers”) of the RoRoSECA project. Task 3.2 falls under the umbrella of Work Package (WP) 3 (entitled “Measures to mitigate or reverse modal shifts”). Task 3.2 is focusing on the policy makers’ available options, and is using tools and models developed in Υear 1 of the RoRoSECA project in order to quantify the implications of the examined measures. It is complementary to Task 3.1 (“Measures from the Ro-Ro operator”) whose report has been delivered in month 19